Cognitive Control and Rumination in Youth: The Importance of Emotion. Issue 3 (November 2014) - Hilt, Lori M.; Leitzke, Brian T.; Pollak, Seth D.
Rumination involves the tendency to passively dwell on negative emotions along with their meanings and consequences. Susan Nolen–Hoeksema demonstrated the role of rumination in the development of several forms of psychopathology and suggested that cognitive control may be one factor that makes some individuals more prone to ruminate than others. Studies with adults have consistently found that rumination is associated with cognitive control difficulties, especially related to switching and inhibiting emotional information. Because rumination predicts psychopathology by adolescence, the present study examined whether ruminating youth would show similar cognitive control difficulties. Fifty–two adolescents completed two tasks from the Cambridge Neuropsychological Test Automated Battery and reported on their depressive symptoms and tendency to ruminate. There was no effect of rumination on a task measuring general cognitive flexibility. However, rumination was associated with difficulty inhibiting negative information when switching from negative to positive blocks on an Affective Go/No–go task. Results suggest both similarities and differences compared to adult studies and are discussed in terms of clinical implications for the prevention and treatment of psychopathology.